Pengelolaan Sampah Di Daya Tarik Wisata Pantai Candikusuma, Desa Candikusuma, Kecamatan Melaya, Kabupaten Jembrana - Made Bagus Megawan; Ida Bagus Suryawan (JURNAL DESTINASI PARIWISATA, 2019)
This research was conducted to find out what kind of waste management is in the tourist attraction of Candikusuma Beach and how much participation and involvment of society in it. Garbage now becomes a crucial problem so it needs to be identified more about it’s management. Waste is a challenge in the implementation of tourism activities. Rubbish need to be addressed in maintaining Cleanliness (Kebersihan) and Beauty (Keindahan) of tourism attraction as an indicator in the Sapta Pesona. The methods used in this research is descriptive qualitative. The technique of determination of informants used is purposive sampling technique. Data sources used are primary and secondary data sources. Primary data in this research is sourced from direct observation to the research location by means of observation and interviews. While secondary data in this research are the data obtained from the documentation or studies library to complement the primary data from the Locus of the reserch. The results of research indicate that the existing waste management in coastal tourist attraction Candikusuma Beach is good, it’s just the involvement of the community in it has not been maximized and less care about coastal cleanliness, the identification process of this management using 3R process among others Reduce, Reuse Recycle. Origin of waste there is a large portion of it coming from the junk mail from upstream. Although there are still many things thet need to be addressed in order to make the management process better and maximum. Keyword : Waste, 3R Process, Society Participation.